Relationship of proctitis and rectal capacity in Crohn's disease. - Buchmann, P (1980)
In patients with Crohn's disease involving the rectum (n=25), there was an inverse relationship between rectal capacity and the degree of proctitis. However, in patients with Crohn's disease not involving the rectum (n=22) the rectal capacity was similar to that of normal controls (n=20). The frequency of defaecation was not related to the degree of proctitis or to the pressure of a colectomy and ileorectal anastomosis. Control subjects had a significantly lower frequency of defaecation than patients with Crohn's disease irrespective of involvement of the rectum.